2006
DOI: 10.1182/blood-2005-11-4639
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of novel tyrosine kinase inhibitor AMN107 and histone deacetylase inhibitor LBH589 against Bcr-Abl–expressing human leukemia cells

Abstract: AMN107 (Novartis Pharmaceuticals, Basel, Switzerland) has potent in vitro and in vivo activity against the unmutated and most common mutant forms of Bcr-Abl. Treatment with the histone deacetylase inhibitor LBH589 (Novartis) depletes Bcr-Abl levels. We determined the effects of AMN107 and/or LBH589 in Bcr-Abl–expressing human K562 and LAMA-84 cells, as well as in primary chronic myelogenous leukemia (CML) cells. AMN107 was more potent than imatinib mesylate (IM) in inhibiting Bcr-Abl tyrosine kinase (TK) activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 54 publications
6
113
1
1
Order By: Relevance
“…In the present studies, we also observed an inhibition of colony growth but not apoptosis of the cultured AML cells following depletion of EZH2 as well as of SUZ12 and EED, by EZH2 siRNA. Treatment with levels of LBH589 and LAQ824 that results in growth arrest, differentiation, and apoptosis was also noted to deplete EZH2, SUZ12, and EED in the CML and AML cells (36,38). However, the precise mechanistic link between the depletion of the PRC2 complex components and LBH589-or LAQ824-induced growth arrest, differentiation, and loss of clonogenic survival was not established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present studies, we also observed an inhibition of colony growth but not apoptosis of the cultured AML cells following depletion of EZH2 as well as of SUZ12 and EED, by EZH2 siRNA. Treatment with levels of LBH589 and LAQ824 that results in growth arrest, differentiation, and apoptosis was also noted to deplete EZH2, SUZ12, and EED in the CML and AML cells (36,38). However, the precise mechanistic link between the depletion of the PRC2 complex components and LBH589-or LAQ824-induced growth arrest, differentiation, and loss of clonogenic survival was not established.…”
Section: Discussionmentioning
confidence: 99%
“…Cell pellets were washed with 1Â PBS, gently resuspended in 200 AL lysis buffer [1% Triton X-100, 1 mmol/L phenylmethylsulfonyl fluoride, 10 Ag/mL leupeptin, 1 Ag/mL pepstatin-A, 2 Ag/mL aprotinin, 20 mmol/L p-nitrophenyl phosphate, 0.5 mmol/L sodium orthovanadate, 1 mmol/L 4-(2-aminoethyl) benzenesulfonylfluoride hydrochloride], and incubated on ice for 30 min as described previously (38). Cell lysates were centrifuged at 12,000 rpm in a tabletop centrifuge for 15 min to remove the nuclear and cellular debris.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the utilization of histone deacetylase inhibitors, together with TKIs, showed a synergistic effect on the level of apoptosis in primary cells isolated from CML patients. 92,93 histone deacetylase inhibitors alone have yet to be successfully translated into clinical therapies for imatinib-resistant CP-or AP-CML patients, but are currently being evaluated together with TKIs in an attempt to modulate minimal residual disease. [94][95][96] Epigenetic methylation can modulate the expression of genes associated with tumor suppression and apoptosis.…”
Section: Spotlightmentioning
confidence: 99%
“…37 Similarly, the number of studies using LBH589 in ALL is very limited. 13,38 An important finding from our study is that the anti-leukemic effect of LBH589 is observed in every cytogenetic subtype of ALL including both T and B-cell ALL as well as patients with Philadelphia-positive ALL. This is in agreement with recent studies, which demonstrate a synergistic effect of HDACi with tyrosine kinase inhibitors such as imatinib or dasatinib.…”
Section: In Vitro Activity Of Lbh589 In All Cellsmentioning
confidence: 62%